Strategi Perencanaan Penyusunan Anggaran Bimbingan Dan Konseling Di Sekolah - Ely, Ramli; Suherman, Uman; Setiawati, Setiawati (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
Budget planning is an important part of guidance and counseling management that should be prepared carefully to support the implementation of guidance and counseling services. This budget must of course be in the school budget. A budget plan that is designed realistically and transparently accountable also supports guidance and counseling services in schools. The guidance and counseling budget design contains all the operational costs and development needs of the guidance and counseling profession. The objectives of the guidance and counseling service program will be achieved by choosing the right management strategy through careful and precise analysis of the available budget.